GURU KREATIF DAN INOVATIF MENGGUNAKAN MEDIA PEMBELAJARAN DI SD NEGERI 18 AMPANG GADANG - Diliza Afrila; Satriyo Pamungkas (LLPM Universitas Deli Sumatera, 2024)
The aim of implementing this community service activity is to improve teachers' abilities in using learning media. The materials and methods for implementing community service activities are training materials and activity methods. The results of this counseling about learning media are as follows: 1) The teacher understands about learning media, 2) The teacher understands the various types of learning media, 3) The teacher understands the basic considerations for selecting and using learning media, 4) The teacher understands the function and use of learning media. The conclusion of this service is that teachers' knowledge and understanding of learning media has increased.